Sutan Takdir Alisjahbana's Thinking, Today and in the Future. Sutan Takdir Alisjahbana as a Literary Writer. - E. Ulrich Kratz (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2008)
Until today, the discussion over Sutan Takdir Alisjahbana's works has still been controversial. On one hand, he was considered pro-West and anti-East, while on the other he was respected as a visionary and a man of principle whose contributions to 20"' century Indonesian intellectual and political life have been essential. Aside from these contradicting views, a thorough study on his lifelong works 1s still rare, and people based their views more on hearsay rather than on their own reading of his writings lhis paper, I hope, will mark an important point in the Indonesian and internation11 nppreciation and recognition ofSutan Takdir Alisjahbana's work. Particularly, I wish to encourage people to actually read his work, rather than to perpetuate , wl'll-established tradition of passing on unsubstantiated views, seemingly as illl' 1cs11lt of an immediate, intellectual conf